"We need to stress them": A case study on an elite football academy`s use of competition to enhance and catalyse the development of footballing talent - Elder, K.; English, C.; Pitkethly, A.; Fountain, H.; Martindale, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction: Professional football is recognised by many as a `results driven business` where competition outcomes are significant and can have a momentous effect on the lives of vast number of people groups. With the increased research in academy football and the development of footballing excellence, it is surprising that still very little is understood about the use of competition within academy programmes and how this reoccurring experience is used to shape and promote the development of footballing ability. Methodology: Six academy coaches and the academy director from an Elite tier Scottish football academy took part in semi-structured, face-to-face interviews at the end of an academy season. Data was subject to inductive, reflexive thematic analysis which ensured trustworthiness of data by utilising processes such as member checking, data triangulation and critical review within the research team. Findings: The competition uses, intentions and objectives of the football academy were analysed and found to fit into one of three categories: 1) playing to learn, 2) learning to win, and 3) playing to win. Findings also highlighted the academy`s `stress, stretch and support` approach to developing talent within competition, and how this approach was operationalised across each stage of the academy. Discussion: Competition was used in a variety of ways within the football academy to promote the development of the academy players` footballing ability. Within the early years of academy football, competition was entirely focused on the development of football specific abilities and understanding with no attention given to the outcome of each competition experience. As players progressed through the academy age groups, a focus on achieving positive competition outcomes was introduced which contributed to the development of an ego-orientated motivational climate within the group and between peers. The academy sought to use competition as a method of assessing the future, first team suitability of academy players. Academy coaches were encouraged to systematically manipulate competition stressors and experiences to stress and stretch the players to observe which players could cope with the need to win in specific games. Competition success and individual statistics were outlined to players as key metrics on which contract offers would be based, thus further ingraining a peer-created, ego-orientated motivational climate within the academy age groups.